IMPROVEMENT OF TECHNOLOGY OF CAST IRON MELTING IN CUPOLA - S. F. Lukashevich; V. K. Filipchik; L. Z. Pisarenko; V. A. Hatskevich (Литьë и металлургия)
The way of cast iron production in cupola-furnace using coke and anthracite in composition of fuel bed is examined. Using of anthracite provides raise of temperature of cast iron and economy of coke.